Reinventing revolution : new social movements and the socialist tradition in India - "Omvedt, Gail" (London, 1993)
This study describes and analyses the new social movements that have arisen in India over the past two decades, in particular the anti-caste movement (of both the untouchables and the lower-middle castes), the women's liberation movement, the farmers' movement (centred on struggles arising out of their integration into a state-controlled capitalist market), and the environmental movements (opposition to destructive development, including resistance to big dam projects and the search for alternatives). Rooted in participant observation, it focuses on the ideologies and self-understanding of the movements themselves. The central themes of this book are the origin of movements in the socio-economic contradictions of post-independence India; their effect on political developments, in particular the disintegration of Congress hegemony; their relation to "traditional Marxist" theory and Communist practice; and their groping toward a synthesis of theory and practice that constitutes a new social vision distinct from traditional Marxism.
Keywords: Social movements-India